KESEHATAN MENTAL PADA PECANDU GAME ONLINE DI DESA KWANGEN GEMOLONG - Purnomosidi, Faqih; Mutiarasari, Adinda Alfia (Universitas Sahid Surakarta, 2021)
In the current era, there are many cases and problems that occur in society because they are influenced by gadgets, especially online games, which are now in high demand. These factors certainly have an impact on the mental health of the community. But people are not aware of their mental health. Online games themselves are very addictive to fans, so not a few addicts lose track of time and forget everything when playing online games. This study aims to understand the mental health of online game addicts using a qualitative approach. The focus of this research is to understand the mental health of online game addicts. In this qualitative research, the model used by the researcher is a case study model. Subjects in this study amounted to 7 people. Subjects in the study are those who are very addicted or commonly called gamers. Games for them are something that is fun, but without them realizing it, games also have their own psychological, physical and even social impacts. Most of those who play games until late at night or even until the morning generally their faces and eyes are glazed look less fresh. This is because their rest time is less awake and less regular eating patterns, they also rarely or never exercise. Games also make them lose track of time and make their emotions rise so they get angry easily.